WhatsApp use in a higher education learning environment: Perspective of students of a Malaysian private university on academic performance and team effectiveness - Lee, Cheng Ean Catherine *; Chern, Huei Huei; Azmir, Dzafran Adris (MDPI, 2023)
The mobile instant messaging application, WhatsApp Messenger (WhatsApp), has become a popular form of communication among adolescents, especially university students, and it has increasingly been used as a tool in collaborative learning in higher education. The use of WhatsApp for education to facilitate ubiquitous learning has been practised worldwide due to its popularity and potential to support teaching and learning processes derived from the diffusion of mobile technology and empowered by the use of smartphones. This study investigates the impact of the use of WhatsApp in a higher education learning environment on students’ perceived academic performance and team effectiveness. A convergent parallel mixed-methods research design was adopted with data collected through a self-administered online survey and two focus group interviews with students of a private university in the Sunway City, Malaysia. The findings of this study present insights into the popularity of WhatsApp among university students and that students use it for social and educational purposes due to its perceived ease of use and usefulness in enhancing academic performance and team effectiveness. Although WhatsApp is recognised as a rich and powerful collaborative tool for students with a positive impact on academic performance, it has a limited impact on the cohesion and openness of team effectiveness.